Distinct Patterns of Urban-Rural and Sex Disparities in Children's BMI Trajectories From 2013 to 2018 - Zhou, Yunping; Yu, Pengli; Zhang, Yanqing; Wang, Tao; Wang, Aimin (Frontiers in Public Health, 2021)
Background: To identify distinct trajectories of body mass index (BMI) in a large sample of Chinese children by urban-rural and sex disparities. Methods: Data for this study were obtained from the National Surveys on Chinese Students' Constitution and Health among 16,060 children aged 6–11 years. Weight and height data were used to calculate BMI. Group-based trajectory modeling (GBTM) was used to identify distinct BMI trajectories. Results: Seven distinct trajectories were identified, “sustained healthy weight” (46.01%), “sustained obesity” (17.26%), “sustained underweight” (4.50%), “obesity to overweight” (6.45%), “obesity to healthy weight” (11.75%), “healthy weight to overweight” (8.67%), and “healthy weight to obesity” (5.36%). The proportions of “sustained obesity,” “healthy weight to obesity,” and “healthy weight to overweight” trajectories were much higher among boys compared with girls (P < 0.001). Meanwhile, children living in rural areas were more represented in the “healthy weight to obesity” trajectory (P < 0.001). Conclusion: In this study, the proportions of BMI development trajectories among 6–11-year-old children varied by sex and urban-rural areas, which may require tailored interventions specifically toward these at-risk trajectories.